Tribology and applications of self-lubricating materials - Omrani, Emad; Rohatgi, P. K.; Menezes, Pradeep L. (CRC Press, 2018)
"Tribology and Applications of Self-Lubricating Materials provides insight into the complex mechanisms behind the development of self-lubricating materials, which due to their ability to transfer embedded solid lubricants to the contact surface to decrease wear rate and friction in the absence of an external lubricant, make up an important part of engineering materials used today. This book emphasizes an understanding of the tribological nature of different composites such as metal, polymer, and ceramic matrix composites and discusses the compatibility of these composites with specific lubricants. The book also offers a view of advancements in the development of self-lubricating mechanisms and covers the latest technologies in the field."--Provided by publisher